6-Formylindolo(3, 2-b)carbazole induced aryl hydrocarbon receptor activation prevents intestinal barrier dysfunction through regulation of claudin-2 expression. (25th May 2018) - Ma, Yuanhang; Wang, Qimeng; Yu, Kun; Fan, Xin; Xiao, Weidong; Cai, Yujiao; Xu, Pengyuan; Yu, Min; Yang, Hua
Abstract: 6-Formylindolo(3, 2- b )carbazole (FICZ), a high-affinity aryl hydrocarbon receptor (AhR) ligand, plays a protective role in inflammatory bowel disease (IBD) through activation of AhR. Interleukin-6 (IL-6) induced intestinal epithelial barrier dysfunction is involved in the pathological process of IBD. In this study, we investigated the protective effects of FICZ on IL-6 induced intestinal epithelial barrier injury. Our data show that AhR activation by FICZ ameliorated colonic inflammation, decreased IL-6 and claudin-2 expression, and maintained intestinal barrier function in a mouse model of dextran sulphate sodium (DSS)-induced colitis. In Caco-2 and T84 intestinal epithelial cells, FICZ also prevented the increase of intestinal epithelial permeability and claudin-2 expression induced by IL-6. Depletion of AhR expression by small interfering (si)RNA reversed FICZ induced decrease of claudin-2. Furthermore, IL-6 induced upregulation of claudin-2 was required for increased caudal-related homeobox 2 (CDX-2) and hepatocyte-nuclear factor (HNF)-1α. However, FICZ repressed the increase of CDX-2 and HNF-1α expression induced by IL-6. These results reveal the protective effects of FICZ on IL-6 induced disruption of intestinal epithelial barrier function through suppressing the expression of claudin-2. In addition, CDX-2 and HNF-1α are involved in the regulation of claudin-2 after IL-6 and FICZ treatment. Therefore compounds related to AhR ligands may be potential pharmaceutical agents to treat IBD. Highlights: FICZ ameliorates colonic inflammation in a mouse model of DSS-induced colitis. FICZ maintains intestinal barrier function both in vivo and in vitro . FICZ decreases claudin-2 expression both in DSS-induced colitis and IL-6 treated cells. Depletion of AhR expression by siRNA reverses FICZ induced decrease of claudin-2. FICZ represses the increase of CDX-2 and HNF-1α expression induced by IL-6.